2010
DOI: 10.1519/jsc.0b013e3181d09e87
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Quadriceps and Hamstrings Proprioceptive Neuromuscular Facilitation Stretching on Knee Movement Sensation

Abstract: Stretching before competition has traditionally been thought to benefit performance; however, recent evidence demonstrating reduced muscle force and power immediately after stretching suggests otherwise. We hypothesized that knee joint position sense would be diminished immediately after proprioceptive neuromuscular facilitation (PNF) stretching to the hamstrings and quadriceps. Eighteen subjects (aged 18-30 years) were seated with their dominant foot attached to a motorized arm with the knee flexed at 135 deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…PS has been mentioned in many previous studies as having an effect on muscle strength reduction. The force reduction occurs as a result of a change in the length-tension relationship, reduction in neural drive, and perception of joint position [18,19]. In our current experiment, this did not have a significant effect on the improvement of muscle strength during manual stretching.…”
Section: Discussionmentioning
confidence: 42%
“…PS has been mentioned in many previous studies as having an effect on muscle strength reduction. The force reduction occurs as a result of a change in the length-tension relationship, reduction in neural drive, and perception of joint position [18,19]. In our current experiment, this did not have a significant effect on the improvement of muscle strength during manual stretching.…”
Section: Discussionmentioning
confidence: 42%
“…Researchers have examined the effect of warm-ups consisting of jogging and stretching exercise or only stretching exercise on knee joint proprioception [ 22 , 28 , 29 ]. Knee joint proprioception did not change after stretching and one study demonstrated that the PNF increases knee movement errors [ 28 ]. Similarly, our study found no improvement on proprioception in LEC and decreased proprioception of knee movements in both the jogging and DS groups.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, our study found no improvement on proprioception in LEC and decreased proprioception of knee movements in both the jogging and DS groups. It has been speculated that stretching of the hamstring and quadriceps may reduce muscle stiffness [ 28 ] and reduce sensitivity of the muscle spindle activity [ 30 ]. Specifically, the acute decrease in muscle strength following stretching could apparently affect proprioceptive sensitivity of the muscle [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Order of testing for the movements to dorsiflexion and plantarflexion was randomized, with all participants undergoing the same testing order. Mean JAR was calculated and presented as absolute error, reflecting the total number of degrees away from the target angle, and as relative error with positive and negative values representing the degrees of overshoot and undershoot, respectively [ 20 ].…”
Section: Methodsmentioning
confidence: 99%